Diversity, Distribution and Conservation Status of the Genus Tectaria Cav. from Deccan Peninsula and Western Ghats of India - Sachin M. PATIL; Raju ANTONY; Santhosh NAMPY; Kishore S. RAJPUT (Notulae Scientia Biologicae, 2019)
The halberd fern genus Tectaria Cav., is terrestrial, medium to large size herb, growing along the cut edges of hills and hillocks or edges of river. It is characterized by the presence of erect, creeping or suberect rhizome with dimorphic, subdimorphic or monomorphic fronds and anastomosing to free veins. Generally, it occurs in different habitats of the tropical to subtropical region of the world. Different members are exploited for various purposes in traditional medicinal system by local tribes. However, the diversity, distribution, conservation status and state of the knowledge about Tectaria (Tectariaceae) is not uniform worldwide including India. Therefore, the present investigation aims to study the diversity, distribution and conservation status of this genus from Peninsula and Western Ghats of India. Out of 24 species reported from India, nearly nine species occur in Deccan Peninsula and Western Ghats. A detailed distribution and conservation status with the identification key to the species of Tectaria distributed in this region is provided herewith.